2003
DOI: 10.1021/bp020136w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Azo Dyes by Manganese Peroxidase under Optimized Conditions

Abstract: The application of enzyme-based systems in waste treatment is unusual, given that many drawbacks are derived from their use, including low efficiency, high costs and easy deactivation of the enzyme. The goal of this study is the development of a degradation system based on the use of the ligninolytic enzyme manganese peroxidase (MnP) for the degradation of azo dyes. The experimental work also includes the optimization of the process, with the objective of determining the influence of specific physicochemical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…Likewise halophenols [178][179][180][181][182] bisphenol A, [183][184][185] various hormones and so-called endocrine disrupting compounds [186][187][188] or even TNT [189,190] have been reported. Non-phenolic compounds may be ‗inactivated' using the LMS or PMS strategy [36,[191][192][193][194][195][196][197][198].…”
Section: Phenol Detoxificationmentioning
confidence: 99%
“…Likewise halophenols [178][179][180][181][182] bisphenol A, [183][184][185] various hormones and so-called endocrine disrupting compounds [186][187][188] or even TNT [189,190] have been reported. Non-phenolic compounds may be ‗inactivated' using the LMS or PMS strategy [36,[191][192][193][194][195][196][197][198].…”
Section: Phenol Detoxificationmentioning
confidence: 99%
“…Previous studies have demonstrated that MnP, with its cofactors in adequate concentration, can degrade azo dye Orange II, reaching 90% decolorization in a relatively short period of time [109]. Phanerochaete chrysosporium, Phanerochaete ostreatus, Trametes versicolor, and Aureobasidium pullulans were screened for degradation of sulfonic azo dyes.…”
Section: Degradation Of Azo Dyes By Filamentous Fungi and Yeastsmentioning
confidence: 99%
“…see Young & Yu 1997, Gunther et al 1998, Kim et al 1998, Ferreira et al 2000, Verma & Madamwar 2002, Mielgo et al 2003, Mohorcic et al 2006, Ferreira-Leitoa et al 2007, Tinoco et al 2007). Whilst application of enzyme solutions to such compounds have shown their effectiveness, living fungal cultures are better applied for bioremediation of contaminated soils and other materials and for purification of aqueous solutions since they produce the necessary enzymes together with H2O2 due to the action of the auxiallary enzyme machinery of lignocellulose degradation (Pointing 2001, Gianfreda & Rao 2004, Tortella et al 2005, Śušla & Svobodová 2006.…”
Section: Peroxidasesmentioning
confidence: 99%